OPTIMASI PRODUKSI N-ACYLHOMOSERINE LACTONASE OLEH ESCHERICHIA COLI BL21 (DE3) YANG DITRANSFORMASIKAN PLASMID BACILLUS LICHENIFORMIS DAHB1 MENGGUNAKAN SISTEM FERMENTASI FED-BATCH SECARA BULK FEEDING DENGAN VARIASI KONSENTRASI GLISEROL - Angelique Pranata, Audrey
Acute hepatopancreatic necrosis disease (AHPND) is a disease that causes hepatopancreatic damage leading to mass mortality in white shrimp (Litopenaeus vannamei). AHPND is caused by Vibrio parahaemolyticus with the pVA1 plasmid (69-70 kbp) that produces the photorabdus insect-related AB (pirAB) toxin through quorum sensing mechanisms. Quorum sensing can be inhibited by Nacylhomoserine lactonase compounds through quorum quenching mechanisms. Nacylhomoserine lactonase can be secreted by E. coli BL21 (DE3) transformed with the pET-26b(+)-N20-aiiA-6xHis plasmid. The transformed E. coli is grown in modified Luria Bertani medium with glycerol as the carbon substrate. Previous research successfully secreted N-acylhomoserine lactonase from the transformed E. coli through batch fermentation with a protein yield of 11.385 mg/ml. Meanwhile, fed-batch fermentation with a glycerol concentration of 400 g/L was able to produce the target plasmid yield optimally at 10186.5 µg/L. Therefore, in this study, optimization was conducted with glycerol concentrations ranging from 300 g/L to 600 g/L. This study aimed to determine the optimal glycerol concentration for the yield of extracellular fraction protein and its growth kinetics data. The results showed that an increase in glycerol concentration did not significantly affect the cell growth kinetics. However, the increase in glycerol concentration decreased the protein yield due to oxygen limitation, leading to a shift towards anaerobic fermentation metabolism. The optimal glycerol concentration was found to be 300 g/L, with the highest protein yield of 13.121 mg/ml. Therefore, the addition of 300 g/L glycerol in bulk feeding medium has the potential to produce high yields of recombinant protein by E. coli BL21 (DE3)